A novel protein encoded by circASK1 ameliorates gefitinib resistance in lung adenocarcinoma by competitively activating ASK1-dependent apoptosis. (1st November 2021) - Wang, Tingting; Liu, Zhenchuan; She, Yunlang; Deng, Jiajun; Zhong, Yifan; Zhao, Mengmeng; Li, Shenghui; Xie, Dong; Sun, Xiwen; Hu, Xuefei; Chen, Chang
Abstract: Acquired resistance to growth factor receptor tyrosine kinase inhibitors limits the therapeutic benefits gained by EGFR-mutant lung adenocarcinoma (LUAD) patients treated with gefitinib. Circular RNAs (circRNAs) are novel noncoding RNAs implicated in the regulation of chemoresistance in malignancies. However, whether circRNAs participate in the development of EGFR-TKI resistance in LUAD remains to be clarified. Here, we report that circASK1 (hsa_circ_0007798) is significantly downregulated in gefitinib-resistant cells and enhances the gefitinib sensitivity of LUAD cells. Mechanistically, we identified a novel protein encoded by circASK1, ASK1-272a.a, which is essential for ASK1/JNK/p38 signaling activation and mediates the chemosensitivity-inducing effect of circASK1 in LUAD. Importantly, this novel isoform competes with ASK1 for binding to Akt1, therefore antagonizing Akt1-induced ASK1 phosphorylation and inactivation, leading to the activation of ASK1-induced apoptosis and alleviating gefitinib resistance. Moreover, increased YTHDF2-mediated endoribonucleolytic cleavage of m 6 A-modified circASK1 accounts for its downregulation in gefitinib-resistant cells. The clinical data and in vivo model further corroborated the suppressive effect of circASK1 and its encoded protein on gefitinib resistance. Our study provides a novel therapeutic target to overcome gefitinib resistance in LUAD patients. Highlights: circASK1 is downregulated in gefitinib-resistant LUAD cells. circASK1 alleviates gefitinib resistance through a novel encoded protein, ASK1-272a.a. ASK1-272a.a compensates for the activation of ASK1-mediated apoptosis by sponging Akt1. High ASK1-272a.a and circASK1 levels are associated with a favorable response to gefitinib.